Geometric risk factors associated with noncontact anterior cruciate ligament graft rupture - Levins, J. L.; Sturnick, D. R.; Argentieri, E. C.; Gardner-Morse, M.; Vacek, P. M.; Desarno, M. J.; Tourville, T. W.; Slauterbeck, J. R.; Beynnon, B. D. (The American Journal of Sports Medicine, 2016)
Background: Anterior cruciate ligament (ACL) graft rupture occurs at a high rate, especially in young athletes. The geometries of the tibial plateau and femoral intercondylar notch are risk factors for first-time ACL injury; however, little is known about the relationship between these geometries and risk of ACL graft rupture. Hypothesis: The geometric risk factors for noncontact graft rupture are similar to those previously identified for first-time noncontact ACL injury, and sex-specific differences exist. Study Design: Case-control study; Level of evidence, 3. Methods: Eleven subjects who suffered a noncontact ACL graft rupture and 44 subjects who underwent ACL reconstruction but did not experience graft rupture were included in the study. Using magnetic resonance imaging, the geometries of the tibial plateau subchondral bone, articular cartilage, meniscus, tibial spines, and femoral notch were measured. Risk factors associated with ACL graft rupture were identified using Cox regression. Results: The following were associated with increased risk of ACL graft injury in males: increased posterior-inferior-directed slope of the articular cartilage in the lateral tibial plateau measured at 2 locations (hazard ratio [HR] = 1.50, P = .029; HR = 1.39, P = .006), increased volume (HR = 1.45, P = .01) and anteroposterior length (HR = 1.34, P = .0023) of the medial tibial spine, and increased length (HR = 1.18, P = .0005) and mediolateral width (HR = 2.19, P = .0004) of the lateral tibial spine. In females, the following were associated with increased risk of injury: decreased volume (HR = 0.45, P = .02) and height (HR = 0.46, P = .02) of the medial tibial spine, decreased slope of the lateral tibial subchondral bone (HR = 0.72, P = .01), decreased height of the posterior horn of the medial meniscus (HR = 0.09, P = .001), and decreased intercondylar notch width at the anterior attachment of the ACL (HR = 0.72, P = .02). Conclusion: The geometric risk factors for ACL graft rupture are different for males and females. For females, a decreased femoral intercondylar notch width and a decreased height of the posterior medial meniscus were risk factors for ACL graft rupture that have also been found to be risk factors for first-time injury. There were no risk factors in common between ACL graft injury and first-time ACL injury for males.